Strategi Transformasi dan Implementasi Human Capital Readiness pada PT PLN - Sari, Wan Variani Permata; Anggarani, Ari (BUDGETING : Journal of Business, Management and Accounting, 2024)
Facing the complex dynamics of the energy industry, PT Perusahaan Listrik Negara (PLN) has strategically formulated a subholding strategy to enhance operational efficiency, optimize asset utilization, and improve service quality to customers. Moreover, fostering human capital readiness has been a crucial focus for PLN to ensure its workforce possesses the skills and knowledge necessary to adapt to the rapid changes in the industry. Evaluating these development programs is an integral part of the human capital fostering strategy. Thus, this paper highlights PLN's efforts to enhance its competitiveness in an increasingly competitive and dynamic energy market. Keywords: Industri Energi, Kesiapan Berubah, Kesiapan Sumber Daya Manusia, Strategi Subholding, PT PLN.